SPSS/PC+ studentware plus - Noruésis, M. J. (Marija J.) 1948- (SPSS Inc., 1991)
A student version of the SPSS/PC+ system. Contains the tools for preparing the statistical analyses most frequently encountered in both classroom and professional environments. Allows students to store and analyze up to fifty variables and an unlimited number of cases.